Study of Double Role Phenomenology Students Who Ever Take Academic Leaves In Nursing Study Program Waingapu - MADIK, ARAB K; KODY, MARTHA METI; GUNAWAN, YOSEPHINA ELIZABETH SUMARTINI; SUKARTININGIH, MARIA CH. E (JURNAL KESEHATAN PRIMER, 2017)
Introduction: Married is generally done by those who have completed the study period or have entered the workforce. But it can not be denied anyway, lately marriage in the study period of students more frequent. This is an interesting phenomenon because it can be ascertained that a marriage bond is done, then the student will certainly have a dual role in his life. He is not only a role as a student with the demands and tasks of college but also directly will have additional demands as a member of the family either be a husband or a wife. Method: The type of research used is qualitative research by way of sampling using purposive sampling. Result: In this research found two themes, namely the role of a student and the role of a housewife. Summary: It is concluded that the role as a student has been run well as it has been expressed by the participants who are happy to have a lot of knowledge, like to get knowledge, gain experience, can add insight, fight for my future and family, can learn and understand who do not know and role as housewife has been run well as already expressed by the participant that is relationship with husband no problem, husband helps to keep child, relationship with good child, sometimes worry because not participant who take care of their own child, relationship with good family, mutual respect, respect and mutual support.